SYSTEM OF CRITERIA AND INDICATORS FOR THE DEVELOPMENT OF MASS SPORTS - Milkevich, O.A.; Sokolskaya, L.V.; Butyaykin, I.A.; Reznikov, A.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to formulate the concept of "mass sport" based on the analysis of Russian legislation, scientific literature and statistical data and develop a system of criteria and indicators for the development of mass sports to assess the quality of services provided by sports and recreation organizations and individual entrepreneurs in the field of mass sports. Methods and structure of the study. When writing the article, general scientific and private scientific methods were used, including the method of analysis and synthesis, statistical (relative to quantitative indicators), survey methods (using google forms for ease of processing and minimizing time), expert assessment and self-assessment (the participants themselves act as experts classes). Results and conclusions. The authors, after analyzing modern legislation and scientific literature, formulated proposals for amending paragraph 4 of art 2 of the Federal Law "On Physical Culture and Sports". The authors propose to consider the provisions on physical culture and mass sports enshrined in this Law as indicators of a meaningful criterion for the development of mass sports. The result of a sociological study on the Microsoft Forms platform (550 respondents from all federal districts of the Russian Federation took part in the survey) is the author’s system of criteria and indicators of mass sports, which can serve as guidelines for organizing work with youth in organizations and enterprises, developing programs for organizing family leisure activities, in the activities of trade union organizations in various industries.